A Network Coding Algorithm for Multi-Layered Video Streaming - Kiraly, Z.; Kovacs, E. R. (2011 International Symposium on Networking Coding, 2011)
Multi-layered video streaming considers different quality requirements of the receivers. Network coding has been shown to be a useful tool to increase throughput of multi-layered service compared to simple multicasting. Kim et al. gave a simple effective algorithm using network coding. We generalize their approach and give an algorithm that solves the problem for two layers optimally for certain natural objective functions and prove NP-hardness of the problem for some other objectives, as well as for more than two layers. We also give some new heuristics for three layers.